The effects of normal aging on myelinated nerve fibers in monkey central nervous system - Peters, Alan (Frontiers in Neuroanatomy, 2009)
The effects of aging on myelinated nerve fibers of the central nervous system are complex. Many myelinated nerve fibers in white matter degenerate and are lost, leading to some disconnections between various parts of the central nervous system. Other myelinated nerve fibers are affected differently, because only their sheaths degenerate, leaving the axons intact. Such axons are remyelinated by a series of internodes that are much shorter than the original ones and are composed of thinner sheaths. Thus the myelin-forming cells of the central nervous system, the oligodendrocytes, remain active during aging. Indeed, not only do these neuroglial cell remyelinate axons, with age they also continue to add lamellae to the myelin sheaths of intact nerve fibers, so that sheaths become thicker. It is presumed that the degeneration of myelin sheaths is due to the degeneration of the parent oligodendrocyte, and that the production of increased numbers of internodes as a consequence of remyelination requires additional oligodendrocytes. Whether there is a turnover of oligodendrocytes during life has not been studied in primates, but it has been established that over the life span of the monkey, there is a substantial increase in the numbers of oligodendrocytes. While the loss of some myelinated nerve fibers leads to some disconnections, the degeneration of other myelin sheaths and the subsequent remyelination of axons by shorter internodes slow down the rate conduction along nerve fibers. These changes affect the integrity and timing in neuronal circuits, and there is evidence that they contribute to cognitive decline.